Analisis Wacana Van Dijk: Stigma Negative Netizen Terhadap Caleg DPD RI Jatim Kondang Kusumaning Ayu Pada Akun Tiktok @Matahati News - Sholihin, Irfa Rizqia Febriyanti (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2025)
This research analyzes the negative stigma of netizens towards the candidate for member of the East Java Regional Representative Council (DPD), Kondang Kusuma Ning Ayu, through comments on the TikTok account @selfiyvelz5. This research uses Van Dijk's critical discourse analysis. The goal of this research is to understand how these comments reflect and reinforce negative stigma toward candidates. Data was collected from various comments that reflect disappointment and rejection, especially regarding visual representation and unmet expectations by voters. The results of the analysis show that expectations of candidates are often formed by stereotypes and visual representations, which, when not met, lead to cognitive dissonance and disappointment expressed through various forms of negative comments. The main factors that cause negative stigma to arise are the difference between the candidate's visual representation and reality, as well as high public expectations regarding the candidate's physical characteristics and age. In conclusion, these negative comments not only reflect individual disappointment but also reinforce broader social stereotypes about the appearance and worthiness of political candidates.